Identification of the processes of preparing Individualized Education Programs (IEP) by special education teachers, and of problems encountered therein - AKÇİN, FATMA NUR (My University, 2022)
There are qualitative studies aimed at identifying the problems encountered in the course of preparing individualized education programs (IEP). However, these studies are conducted with only a few participants. There is a need to test the results on a larger sample size. A questionnaire based on findings of interview techniques, used in qualitative research methodology, is developed. Using this questionnaire will identify the actual problems based on wider sample size, creating guidance for the required measures and actions. Thus, the purpose of this study is to identify the processes of preparing individualized education programs by special education teachers and of the problems they encounter. The sample group for this study, which utilized cross-sectional screening methods, is 1,000 teachers working in the special education field. At the end of the study, in addition to characteristics of IEP planning, performance measurement and IEP drafting by teachers, findings on problems faced due to teacher, room, material, parent, student, and personnel, in the course of preparation of IEP, were identified.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Individualized education program; individualized instruction plan; problems; questionnaire; crosssectional screening.